Gut Microbiome Signatures Are Predictive of Cognitive Impairment in Hypertension Patients—A Cohort Study - Qu, Lei; Dong, Zhouyan; Ma, Songcui; Liu, Yaping; Zhou, Wei; Wang, Zitong; Wu, Chen; Ma, Rui; Jiang, Xinze; Zu, Tingting; Cheng, Mei; Wu, Yulong (Frontiers in Microbiology, 2022)
Growing evidence has demonstrated that hypertension was associated with dysbiosis of intestinal flora. Since intestinal microbes could critically regulate neurofunction via the intestinal-brain axis, the study aimed to reveal the role and prediction value of intestinal flora alteration in hypertension-associated cognitive impairment. A cohort of 97 participants included 63 hypertension patients and 34 healthy controls. The structure of intestinal flora was analyzed by V3-V4 16S rRNA amplicon sequencing. The cognitive function was assessed using Montreal Cognitive Assessment (MoCA) scale, and 31 patients were considered to have cognitive impairment (MoCA < 26). Patients with cognitive impairment had considerable alterations in intestinal flora structure, composition, and function compared with normal-cognitive-patients. Especially, the abundance of LPS-containing taxa (Proteobacteria, Gammaproteobacteria, Enterobacterales, Enterobacteriaceae, Escherichia-Shigella) and SCFAs-producing taxon (Prevotella) significantly changed in cognition-impaired patients. Tax4Fun predication results showed down-regulation of glycan biosynthesis and metabolism in the hypertension patients with cognitive impairment. Additionally, the pathway was demonstrated significant correlated with LPS-containing taxa (Proteobacteria, Gammaproteobacteria, Enterobacterales, Enterobacteriaceae, Escherichia-Shigella) and SCFAs-producing taxon Prevotella. Furthermore, the taxa-based multiple joint prediction model (9x) was demonstrated to have excellent diagnostic potential for cognitive impairment of hypertension patients (AUC = 0.944). The current study revealed the involvement of intestinal microbiota dysbiosis in cognition impaired hypertensive patients and provided an objective predictive index for this cognition disorder.